2022
DOI: 10.3389/fcimb.2022.824101
|View full text |Cite
|
Sign up to set email alerts
|

Commensal Bacteria in the Cystic Fibrosis Airway Microbiome Reduce P. aeruginosa Induced Inflammation

Abstract: Chronic Pseudomonas aeruginosa infections play an important role in the progress of lung disease in patients suffering from cystic fibrosis (CF). Recent studies indicate that polymicrobial microbiome profiles in the airway are associated with less inflammation. Thus, the hypothesis was raised that certain commensal bacteria might protect the host from inflammation. We therefore performed a screening study with commensals isolated from CF airway microbiome samples to identify potential beneficial commensals. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 78 publications
0
22
0
Order By: Relevance
“…Co-infection models in human epithelial cell lines with P. aeruginosa and commensal CF microbiota have shown that different strains of Streptococcus mitis reduce P. aeruginosa -induced inflammation through reduction of interleukin 8 (IL-8) production and neutrophil extracellular trap (NET) formation. The mechanism of action is still unknown but thought to be through modification of the micro-environment by metabolism adjustment by the commensal bacteria [ 55 ]. In contrast, some oral commensal streptococci enhance P. aeruginosa pathogenicity by increasing its virulence factor expression (eg, pyocyanin and elastase) [ 4 , 56 , 57 ].…”
Section: Who Are the Microbial Players?mentioning
confidence: 99%
See 1 more Smart Citation
“…Co-infection models in human epithelial cell lines with P. aeruginosa and commensal CF microbiota have shown that different strains of Streptococcus mitis reduce P. aeruginosa -induced inflammation through reduction of interleukin 8 (IL-8) production and neutrophil extracellular trap (NET) formation. The mechanism of action is still unknown but thought to be through modification of the micro-environment by metabolism adjustment by the commensal bacteria [ 55 ]. In contrast, some oral commensal streptococci enhance P. aeruginosa pathogenicity by increasing its virulence factor expression (eg, pyocyanin and elastase) [ 4 , 56 , 57 ].…”
Section: Who Are the Microbial Players?mentioning
confidence: 99%
“…Although most studies to date have identified interactions that increase virulence of CF pathogens, it is expected that antagonistic interactions abound. Recently, in vitro data have demonstrated that several commensal isolates of Streptococcus mitis and Streptococcus oralis from sputum can reduce pro-inflammatory responses of patient-derived airway epithelial cells to P. aeruginosa [ 55 ]. Importantly, these findings were strain, not species, specific further highlighting the need for detailed profiling beyond 16S community level in the CF microbiome.…”
Section: Polymicrobial Interactions and Virulencementioning
confidence: 99%
“…The presence of thick mucus and the vicious cycle of infection and inflammation has an impact on the lung microbiome in patients with CF [ 9 ]. The interaction between different bacteria in the lungs of patients with CF may be associated with the severity of inflammation in the lungs [ 9 ].…”
Section: Role Of Infection In the Development And Progression Of Cyst...mentioning
confidence: 99%
“…The presence of thick mucus and the vicious cycle of infection and inflammation has an impact on the lung microbiome in patients with CF [ 9 ]. The interaction between different bacteria in the lungs of patients with CF may be associated with the severity of inflammation in the lungs [ 9 ]. There are conflicting data on the role of different bacterial species, especially the role of facultative anaerobes of the usually so-called “oropharyngeal flora” in the lung of individuals with CF and if the interactions lead to more or less infection and inflammation [ 10 ].…”
Section: Role Of Infection In the Development And Progression Of Cyst...mentioning
confidence: 99%
See 1 more Smart Citation